The Use of E-Money During the Covid-19 Pandemic: Attitudes and Interests of Balinese People - Yuliastuti, Ida Ayu Nyoman; Kepramareni, Putu; Bhegawati, Desak Ayu Sriary; Purnawati, Ni Luh Gede Putu (Universitas Mercu Buana, 2022)
Objectives: The objective of this research is to review and analyze the impact of perceived ease of use, perceived usefulness, and perceived risk on attitude toward using and intention to use e-money during the Covid-19 pandemic.Methodology: The example utilized upwards of 115 respondents with an accidental sampling method and the data were processed and analyzed using SEM-PLS.Finding: The outcomes showed that intentions to use e-money were influenced by perceived ease of use, perceived usefulness, and attitude toward using, while perceived risk didn't influence attitude toward using and intention to use e-money.Conclusion: The use of e-money has increased because e-money can provide more convenience and benefits in reducing the risk of spreading covid-19. The utilization of e-money additionally turns out to be more compelling when there is social removal so that dangers, for example, network interruption and security presently don't influence the utilization of e-money.